Caracterización de la abeja sin aguijón (Geotrigona leucogastra) en el sitio rambuche del cantón Jama - Padilla Arroyo, Roxana Estefanía (2023)
The stingless bee Geotrinona leucogastra belongs to the Meliponini tribe of the genus Geotrigona. It lives in the soil, its products such as pollen, honey, and propolis are valued in the community and for being a pollinator of native trees, hence the environmental importance in the expansion of fields for agriculture and livestock, for this reason the present The work was carried out in the Rambuche Site of the Jama canton to determine the characteristics that established the conservation measures that ensure survival and biodiversity. Five hives were studied, an average temperature of 34.8°C (±1.30°C) was detected, average humidity 13.90°C (±1.43°C), the depth of the nests 1.03m (±0.35m). To determine the morphology, five worker bees were captured for the study, the length of the head had an average of 1.91mm (±0.40mm), the thorax 1.84mm (±0.55mm), the legs and average of 0.24mm (±0.04mm), and the abdomen 1.73mm (±0.50mm). The average flight range was 60m (±89.44m). Two liters of honey were collected for bromatological analysis, as acidity expressed in 7.33kg formic acid, 0.14g ashes was found; moisture 42.09g; pH at 25°C/25°C of 2.54, protein 0.32g; 1.18g fructose; glucose 10.75g; maltose 4.70g; sucrose 0.25g. It is important to protect this species since it ensures the survival of the native flora of the region, thus contributing to the pollination of de flawers.